Problematika Pengawasan Kesyariahan Peer-to-Peer Fintech Syariah: Analisis POJK Nomor 10/POJK.05/2022 dan Peran DSN MUI - Regita, Ria (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the regulatory issues in the supervision of Sharia compliance within the Peer-to-Peer (P2P) Sharia Fintech system, particularly in the implementation of Financial Services Authority Regulation (POJK) Number 10/POJK.05/2022. The contribution of this research includes strengthening Sharia fintech regulations through more specific and collaborative supervisory recommendations between the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This article falls under qualitative library research using a normative legal study method. It examines legal rules, regulations, and fatwas while evaluating the effectiveness of Sharia compliance supervision in practice. The findings indicate that the supervision mechanism of Sharia fintech remains weak due to the lack of direct monitoring by OJK and DSN-MUI, the absence of binding supervisory standards, and the reliance on internal reports from fintech platforms. Strengthening OJK's role in establishing stricter Sharia supervision guidelines and implementing a periodic audit system is necessary to ensure compliance with Sharia principles.